AN EXPERIMENTAL STUDY ON POLYMER IMPREGNATED CONCRETE USING STEEL WIRE MESH - Ramesh Kumar, G.B.; Rishab Narayanan, V (International Journal of Psychosocial Rehabilitation, 2020)
In general, there are many materials available for enhancing the strength of the concrete. Partially polymer is used for improving the strength, but it is not commonly used. There is much research done for better improvement of the strength of concrete by using polymers. The study inspects the compressive strength, flexural strength, and split tensile strength of M20, M40, and M60 with polymer-impregnated concrete and steel wire mesh. There will be a comparison between PCC (plain cement concrete), PCC (steel wire mesh), and polymer impregnated concrete. Polymer impregnated concrete is obtained by introducing monomer in concrete by socking at atmospheric pressure. The monomer will be replaced in air voids of concrete. Ferrocement is the combination of mortar and steel wire mesh. To improve the strength of the concrete, the steel wire is used. The test done in two stages of the cube, prism, and cylinder was conducted in 7 days and 28 days, and the water-to-cement ratio is taken at 0.45; cement is used in OPC 53 grade. The moulds are used in cubes, prisms, and cylinders. The compressive, flexural, and split tensile strength tests are conducted in two stages and compared between convectional concrete and polymer-impregnated concrete with steel wire mesh. As a result, the impact of steel wire mesh played a major role in improving the strength of concrete.